A Comparison of Formative Vocabulary Tests as Credited and Non-credited Assessment Tasks: Japanese as a Second/foreign Language at the Tertiary Level. - Hasegawa, Hiroshi (International Journal of Languages, Literature and Linguistics, 2016)
The aim of this research was to identify whether regularly implemented credit-bearing assignment tasks have any influence on students’ learning outcomes and their perceptions of vocabulary learning in Japanese as a second/foreign language education. The target assignment task was vocabulary learning through regularly implemented testing. This was attempted with two research objectives (RO). RO1 was to compare and contrast the differences in the academic results of students required to complete the same vocabulary tests, but with one group doing so for credit and the other not receiving credit. RO2 was to explore the opinions of students who experienced tasks organised in similar situations but with contrasting purposes, namely one purpose being to do the tasks to earn credit and the other not earning credited. The results suggest that the assignment task conditions changed by the university policy to do tasks that are not assessed may have a negative impact on students’ learning. These findings offer strong support for the suggestion to return to the earlier practice of considering credit-bearing assignments for students’ final subject marks.